Implementasi Manajemen Sarana dan Prasarana di Madrasah Tsanawiyah Negeri 2 Deli Serdang - Nurana Dwina Bintang; Makmur Syukri; Afrahul Fadhila Daulai (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to determine the condition of educational facilities and infrastructure, the management of educational facilities and infrastructure, as well as what supporting and inhibiting factors exist in implementing existing facilities and infrastructure at Madrasah Tsanawiyah Negeri 2 Deli Serdang. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews and observations supported by data and documentation such as photos of madrasa facilities and infrastructure. The research subjects are the head of the madrasa, deputy head of the madrasa for facilities and infrastructure and curriculum as well as administrative staff at MTsN 2 Deli Serdang. Data analysis techniques using data collection, data reduction, data presentation and drawing conclusions. Data validity techniques with research expansion, increased persistence, and triangulation.